Risk assessment and security for pipelines, tunnels, and underground rail and transit operations - Doro-on, Anna Maricel, 1977- (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This volume presents an integrated quantitative risk assessment methodology systematically analyzing alternatives for protecting underground rail, oil and gas pipelines, pipeline freight transportation, and other tunnel systems from threats of terrorism and other disasters. The book analyzes engineering, environmental, and economic impacts and addresses both direct and collateral damages. The book also presents regulations, standard processes, and risk assessment models recommended by the US Department of Homeland Security (DHS) and other governmental and state agencies'--
Includes bibliographical references and index.
Keywords: Pipelines -- United States -- Safety measures; Pipelines -- Risk assessment -- United States; Tunnels -- United States -- Safety measures; Tunnels -- Risk assessment -- United States; Transportation -- United States -- Safety measures; Transportation -- Risk assessment -- United States